ANALISIS PERBEDAAN PENDAPATAN ANTARA PETANI PADI SAWAH PENGGUNA IRIGASI POMPANISASASI DAN IRIGASI NON POMPANISASI DI DESA TELANG JAYA KECAMATAN MUARA TELANG KABUPATEN BANYUASIN (JASEP, 2019)
Indonesian is an agricultural country where the majority of poople live in agriculture, this is supported by the fact that the land used by the community as agricultural land, besides that the soil conditions in indonesian have good nutrient content so that it can help plant growth.The purpose of this study was to determine the differences in production and income between wetland rice farmers using pumped irrigation with non-pumping irrigation in Telang Jaya Village, Muara Telang District, Banyuasin Regency, from August to October 2018. The research method used is survey, for the sampling method used is the disproportionate stratified random sampling method, the data collection method used is interview and data processing in this study using quantitative analysis methods.From the research results The average production obtained from the results of rice paddy farming in pumping irrigation users was 6.686 Kg / Ha and non-pumping irrigation use was 6,640 Kg / Ha in Telang Jaya Village, Muara Telang District, Banyuasin Regency and the average income obtained from the results of paddy farming in pumping irrigation users amounted to Rp. 30,434,316 / Ha / MT and non-pumping irrigation users of Rp. 28,249,350 / Ha / MT. So that there is no significant difference in income between rice farmers using pumping irrigation and non pumping irrigation.